Geospatial techniques-based land suitability analysis for sustainable production of major crops in Sile Watershed of Gamo Zone, Southern Ethiopia - Mohammed Nuru; Mulugeta Debele; Adefris Tefera; Abren Gelaw (Heliyon)
Crop farming by smallholder farmers of Ethiopia and Sile Watershed is practiced based on commonsense experiences of farmers. This study was targeted to evaluate the suitability of land for the production of four major crops in Sile Watershed. Data were acquired from sources such as climate data (from CHRS data portal CRU TSv.4.05), slope (via Digital Elevation Model, ASTER 30m), and soil data via GPS-based survey, lab-test and others. Composite sampling was used to collect 43 soil samples (at 30 cm depth) from the upstream (21), midstream (13) and downstream (9), and considering land use/cover classes. Requirements of the four crops were set using manuals and literature. Analytical Hierarchy Process was used to prioritize the multiple criteria used for assessment. The weighted overlay technique was used to analyze and map the suitability levels of the watershed for the four crops using ArcGIS. The results revealed that 51.7 %, 41.7 %, 42.2 % and 35.4 % of Sile watershed was ‘highly suitable’ for the sustainable production of maize, banana, teff and barley, respectively; however, 6.3 %, 27.6 %, 16.3 %, and 4.4 % of the area was not suitable for the production of the respective crops. While the land suitability of maize and banana is confined to the downstream and partly the midstream, the high suitability of barley is limited to the upstream. Nitrogen, phosphorous, organic carbon, soil pH and salinity showed negative correlation with altitude and rainfall at 99 % and 95 % confidence levels. Variable rainfall, salinity and alkalinity are the main constraints of the four crops in the downstream. But slope steepness, organic carbon, phosphorous and nitrogen deficiencies, and soil acidity are the main threats of yield in the upstream and partly the midstream. Thus, stakeholders should be coordinated to apply agronomic, irrigation, structural and vegetative measures for tackling the productivity bottlenecks of Sile watershed, Southern Ethiopia.